2014
DOI: 10.3813/aaa.918739
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of the Geometrical Parameters in the Ultrasonic Transmission Through Plates with Subwavelength Holes Arrays

Abstract: This paper presents an overview of the recents studies on the ultrasonic transmission through subwavelength holes arrays. The role of the geometrical parameters of the perforated plates in the transmission features has been reported by using a theoretical model under the rigid-solid assumption. It is shown that the transmission spectrum can be tailored by varying the geometrical parameters.PACS no. 43.35. +d, 42.79. Dj

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It was demonstrated that there was an interplay between Fabry-Perot resonances inside the holes, lattice resonances in periodic arrays and elastic Lamb modes on the ultrasonic transmission perforated plates with subwavelength holes inmersed in water [9]. The investigations on acoustic transmission through subwavelength apertures restricted to plates perforated with periodic arrays of apertures showed that the geometrical parameters of the hole array are important in the ultrasonic transmission through perforated plates [10][11][12]. Recently, many phenomena regarding the extraordinary acoustic transmission through subwavelength hole arrays have been demonstrated [13][14][15][16][17] The acoustic transmission through a plate perforated with a periodic array (or semiregular tilings) of subwavelength apertures [18] showed strong resonant transmissions that were attributed to the coherent diffraction by the long-range order of the quasiperiodic structure.…”
mentioning
confidence: 99%
“…It was demonstrated that there was an interplay between Fabry-Perot resonances inside the holes, lattice resonances in periodic arrays and elastic Lamb modes on the ultrasonic transmission perforated plates with subwavelength holes inmersed in water [9]. The investigations on acoustic transmission through subwavelength apertures restricted to plates perforated with periodic arrays of apertures showed that the geometrical parameters of the hole array are important in the ultrasonic transmission through perforated plates [10][11][12]. Recently, many phenomena regarding the extraordinary acoustic transmission through subwavelength hole arrays have been demonstrated [13][14][15][16][17] The acoustic transmission through a plate perforated with a periodic array (or semiregular tilings) of subwavelength apertures [18] showed strong resonant transmissions that were attributed to the coherent diffraction by the long-range order of the quasiperiodic structure.…”
mentioning
confidence: 99%